BIOCHEMICAL BASES OF REGENERATIVE POMEGRANATE CULTIVATION - Ergasheva, Farogʻat Sheraliyevna; Kushiyev, Habibjon Xojiboboyevich; Xushmatov, Shunqor Sadullayevich; Xudoynazarov, Muxriddin Shuxrat o‘g‘li; Nuriyeva, Mahbuba Urinbayevna (SCIENCE and SOCIETY, 2026)
The article presents data on the amino acid composition of the fruit peel, seeds, leaves, and flowers of the pomegranate (Punica granatum L.) cultivars "Oq shirin," "Qizil anor," and "Qoraqayin." The study was conducted at the Research Institute of Agrobiotechnology and Biochemistry of Gulistan State University. The results showed that the contents of proline, lysine, threonine, and glycine in the pomegranate peel were 2.8, 2.95, 3.55, and 9.2 g/100 g, respectively, whereas in the seeds these values reached 8.0, 11.6, 32.3, and 43.8 g/100 g, respectively. It was established that the proportion of total amino acids accounted for 72.6% in the seeds and 27.4% in the peel. The proportion of essential amino acids was 25.0% in the seeds and 75.0% in the peel. The amount of essential amino acids in the pomegranate peel was found to be approximately three times higher than that in the seeds.
Keywords: pomegranate seeds; fruit peel; essential amino acids; non-essential amino acids; limiting amino acids; regenerative crop production; regenerative agriculture